NUTRITIONAL STATUS OF PRIMARY SCHOOL CHILDREN WITH MID-DAY MEAL PROGRAM (Proceedings of the International Conference on Public Health, 2021)
This study was conducted to determine the nutritional status of primary school childrenwith the mid-day meal program. A cross-sectional study was conducted in 05 primary schools withthe mid-day meal program of Sundarganj Upazila of Gaibandha district from January 01 toDecember 31, 2017. A total of 357 primary school children of class IV and class V were selectedusing a systematic sampling technique. A semi-structured questionnaire was used to collect datafrom the school children of mid-day meal program schools. The anthropometric measurements suchas weight, height and MUAC were measured for each child individually. Then weight and heightwere used to calculate the Z score to interpret nutritional status. The mean age of children was10.83±1.03 years. The mean weight and mean height of children were 32.40±7.21 kg and141.22±8.52 cm respectively, and the mean MUAC was 19.65±2.31 cm. It was revealed that 91.3%of children were normal by Height for Age (HAZ) and 89.1% were normal by Weight for Age(WAZ), and the remaining children were stunted and underweight respectively. 78.8% of childrenused anthelminthic drugs regularly and among them, 74.3% were normal in Weight for Age Z score.Socioeconomic status, dietary habit, physical activity and anthelminthic use by the child were foundto be determinants of their nutritional status.
Keywords: Mid-day meal, Primary school children, Nutrition, Anthropometric, Stunted, Underweight, School Health